The Decline of Banjar Customary Buying and Selling Contracts in the Era of Online Transactions: A Study of the Living Qur'an in Pahandut Seberang - Aysah; Ahmad Rizky Firdaus; Nur Wakhidah (Aslama: Journal of Islamic Studies, 2025)
This study examines the erosion of the traditional Banjar sales contract (akad) in Pahandut Seberang amid the rapid growth of digital transactions such as GoFood and online shopping. For generations, the Banjar community has upheld the verbal akad expressed through the phrases “jual-lah” (sell it) by the seller and “tukar-lah” (I take it) by the buyer as a symbol of mutual consent, honesty, and ethical conduct in trade. This practice is deeply rooted in Qur’anic values, particularly the principle of tarāḍin (mutual willingness) as stated in Qur’an Surah An-Nisā’ verse 29. However, modernisation and digital technology have caused the verbal akad to diminish, especially in non-face-to-face transactions where ijabqabul is replaced by technical actions such as pressing the “order” button. This research employs a Living Qur’an approach and a qualitative-descriptive method through interviews, observation, and documentation with three informants: a Banjar seller, a GoFood driver, and a buyer. The findings reveal three patterns: (1) traditional sellers continue to preserve the akad as cultural identity and religious practice, (2) digital transactions eliminate verbal akad and transform social relations into impersonal interactions, and (3) buyers reinterpret akad through social expressions such as saying “thank you” as a sign of consent. Thus, the Banjar akad tradition is not entirely disappearing but undergoing a transformation of meaning amid technological change.